Developmental single-cell transcriptomics of hypothalamic POMC neurons reveal the genetic trajectories of multiple neuropeptidergic phenotypes - Yu, Hui (2022)
Proopiomelanocortin (POMC) neurons of the hypothalamic arcuate nucleus are essential to regulate food intake and energy balance. However, the ontogenetic transcriptional programs that specify the identity and functioning of these neurons are poorly understood. Here, we use scRNAseq to define the transcriptomes characterizing Pomc-expressing cells in the developing hypothalamus and TRAP-seq to analyze the subsequent translatomes of mature POMC neurons. Our data showed that Pomc-expressing neurons give rise to multiple developmental pathways expressing different levels of Pomc and unique combinations of transcription factors. The predominant cluster, featured by high levels of Pomc and Prdm12 transcripts represents the canonical arcuate POMC neurons. Additional cell clusters expressing medium or low levels of Pomc mature into different neuronal phenotypes featured by distinct sets of transcription factors, neuropeptides, processing enzymes, cell surface and nuclear receptors. We conclude that the genetic programs specifying the identity and differentiation of arcuate POMC neurons are diverse and generate a heterogeneous repertoire of neuronal phenotypes early in development that continue to mature postnatally.